Treasures of the Russian Ballet Galina Ulanova, Maya Plisetskaya, Vladimir Vasiliev... -- Ballet du Bolshoï - Grigorovich, Yuri; Ivanov, Lev; Nureyev, Rudolf; Adam, Adolphe; Anisimova, Nina; Gorsky, Alexander (BBC, under licence to International Classical Artists Ltd, 2012)
Though ballet had its genesis in the courts of Europe, it was in Russia that it evolved into the art form that we know better today - particularly with the creation of the story ballet or balet-dram culminating in tchaikovsky's Swan Lake, Slepping Beauty and Nutcracker trio of masterworks. Of equal significance was the level of training needed for the dancers to develop the skills, assets and grace required. Nijinsky, Pavlova, Karsavina and Massine are just a few examples of the dancers whose fame has spread internationally. These stars were soon admired outside of Russia, often in tours organised at the last minute. Diaghilev's Ballets had their Paris and London performances in the early 1900s and even undertook a United States tour for the 1916/17 season concluding with performances at New York's Metropolitan Opera House. Fans of Kirov will particularly appreciate the first act of The Stone Flower danced by the main dancers of the early performances.
Keywords: ballet; Webcast; Internet videos; Vidéos sur Internet